Reading and Writing Mistakes among Students of the First Three Grades of Basic Education in the Directorate of the University Brigade due to Some Variables - Abeer Alabdalat (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to investigate reading and writing mistakes among students of the first three grades of basic education in the university's district directorate in light of some variables. The study sample consisted of (218) teachers who were chosen in a simple random way from public and private schools. To collect the study data, two questionnaires were built. The first dealt with reading mistakes consisting of (18) items, and the second dealt with written mistakes consisting of (22) items. The results of the study showed that the most common reading mistakes for students in the first three grades are: mistakes in pronouncing movements related to the structure of the word, adherence to the requirements of punctuation marks, and confusing (Lam Al-shamsiyah) and (Lam Al-Qamaryah). The most common written mistakes are poor writing of hamzas of all kinds, confusion between (Lam Al-Shamsyah) and (Lam Al-Qamaryah), and writing a thousand compiled alpha elongated and vice versa. It also showed that there were statistically significant differences in the teachers' estimates of the reading errors faced by the primary stage students due to the variable of the school type and in favor of the government school. There are statistically significant differences in the teachers' estimates of the written errors due to the gender and school type variables and in favor of the government school. The researcher recommends the necessity of teachers of specialized Arabic language teaching basic stage, and holding training workshops for teachers on methods of teaching spelling.